2013
DOI: 10.1097/igc.0b013e3182a80b14
|View full text |Cite
|
Sign up to set email alerts
|

Atl

Abstract: The patients with p16-positive CIN1 had an increased risk for progression that was concentrated in the first year of follow-up. Immunostaining of p16 could have a role in short-term surveillance of patients with CIN1. Further research should focus on midterm/long-term outcomes of p16-positive CIN1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Some of these studies do not include hrHPV testing, 4,16 have a short follow-up, 21 or include a very limited number of patients with LSIL/CIN1. 25,26 Other studies analyze specific groups, which were retrospectively selected based on the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these studies do not include hrHPV testing, 4,16 have a short follow-up, 21 or include a very limited number of patients with LSIL/CIN1. 25,26 Other studies analyze specific groups, which were retrospectively selected based on the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, a number of studies have addressed this issue and have suggested that p16-positive LSIL/CIN1 lesions are at higher risk of showing a HSIL/CIN2-3 outcome diagnosis. 4,5,16,17 However, the number of cases included in these series was very small and consequently, the true value of p16 as a marker of 'progression' in these women remains uncertain. Thus, prospective, longitudinal studies focused on the prognostic value of p16 immunostaining in patients with biopsies showing LSIL/CIN1 are needed before definitive conclusions can be drawn.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional analyses are employed to monitor cellular (host) proteins whose synthesis in cervical lesions is de-regulated upon p53 and pRb functional inactivation. These include the cyclin-dependent kinase inhibitor p16INK4a and the proliferation antigen Ki-67 ( Figure 1 ) [ 47 , 48 , 49 ]. In particular, the progression of CIN lesions can be predicted by the combination of low pRb/p53 and high Ki-67/p16INK4a expression in the basal layers of the cervical epithelium [ 47 , 48 , 49 ].…”
Section: Role Of the Hpv-e5 E6 And E7 Proteins In The Developmentmentioning
confidence: 99%
“…These include the cyclin-dependent kinase inhibitor p16INK4a and the proliferation antigen Ki-67 ( Figure 1 ) [ 47 , 48 , 49 ]. In particular, the progression of CIN lesions can be predicted by the combination of low pRb/p53 and high Ki-67/p16INK4a expression in the basal layers of the cervical epithelium [ 47 , 48 , 49 ]. Recent data suggest evaluating the profile of specific cellular micro-RNAs that have an important role in cervical carcinogenesis and are modulated by the E5, E6 or E7 proteins of HR-HPV [ 50 ].…”
Section: Role Of the Hpv-e5 E6 And E7 Proteins In The Developmentmentioning
confidence: 99%